INTERNATIONAL COMMUNITY SERVICE PROGRAM THROUGH ACADEMIC COLLABORATION AND INDUSTRIAL EXPOSURE IN MALAYSIA: STRENGTHENING GLOBAL NETWORKING AND HIGHER EDUCATION INTERNATIONALIZATION - Nuryati Nuryati; Furtasan Ali Yusuf; Eva Aqilah Abu Jalil; Saprudin Saprudin; Suheri Suheri; Sri Nuraida; Mad Uma; Rizqon Nujuludin; Matlaul Anwar; Evi Gustini; Supriyadi Supriyadi; Tuti Alawiah; Nurul Dewi Hayati (International Journal of Engagement and Empowerment (IJE2), 2025)
The internationalization of higher education has become a strategic agenda for universities in enhancing academic quality and global competitiveness. This community service program (PKM) was conducted in Malaysia from 2–5 September 2026 by the Association of Indonesian Lecturers (IDDRI) Banten Province involving delegates from several Indonesian universities. The activities included international seminars, academic discussions, institutional visits, signing of Memoranda of Understanding (MoU) with Management and Science University (MSU) and SEGi University, and industrial visits to Kumpulan Media Karangkraf. The program employed participatory and collaborative approaches through knowledge sharing, academic networking, and experiential learning. The results indicated significant achievements in strengthening international partnerships, increasing participants’ global perspectives, expanding opportunities for collaborative research and publications, and enhancing institutional networking. The program demonstrates that international community engagement can effectively support higher education internationalization and contribute to sustainable academic collaboration.